Iron-sulfur cluster binding by mitochondrial monothiol glutaredoxin-1 of trypanosoma brucei: molecular basis of iron-sulfur cluster coordination and relevance for parasite infectivity - Manta, Bruno; Pavan, Carlo; Sturlese, Mattia; Medeiros, Andrea; Crispo, Martina; Berndt, Carsten; Krauth-Siegel, Renate; Bellanda, Massimo; Comini, Marcelo A. (Antioxidants & redox signaling, 2013)
Aims: Monothiol glutaredoxins (1-C-Grxs) are small proteins linked to the cellular iron and redox metabolism. Trypanosoma brucei brucei, model organism for human African trypanosomiasis, expresses three 1-C-Grxs. 1-C-Grx1 is a highly abundant mitochondrial protein capable to bind an iron-sulfur cluster (ISC) in vitro using glutathione (GSH) as cofactor. We here report on the functional and structural analysis of 1-C-Grx1 in relation to its ISC-binding properties. Results: An N-terminal extension unique to 1-C-Grx1 from trypanosomatids affects the oligomeric structure and the ISC-binding capacity of the protein. The active-site Cys104 is essential for ISC binding, and the parasite-specific glutathionylspermidine and trypanothione can replace GSH as the ligands of the ISC. Interestingly, trypanothione forms stable protein-free ISC species that in vitro are incorporated into the dithiol T. brucei 2-C-Grx1, but not 1-C-Grx1. Overexpression of the C104S mutant of 1-C-Grx1 impairs disease progression in a mouse model. The structure of the Grx-domain of 1-C-Grx1 was solved by nuclear magnetic resonance spectroscopy. Despite the fact that several residues—which in other 1-C-Grxs are involved in the noncovalent binding of GSH—are conserved, different physicochemical approaches did not reveal any specific interaction between 1-C-Grx1 and free thiol ligands. Innovation: Parasite Grxs are able to coordinate an ISC formed with trypanothione, suggesting a new mechanism of ISC binding and a novel function for the parasite-specific dithiol. The first 3D structure and in vivo relevance of a 1-C-Grx from a pathogenic protozoan are reported. Conclusion:T. brucei 1-C-Grx1 is indispensable for mammalian parasitism and utilizes a new mechanism for ISC binding. Antioxid. Redox Signal. 19, 665-682.
Gesehen am 22.06.2021